Organosilicon marine antifouling paint with self-adhesion property
By introducing modified polysiloxane copolymer and catechol structure carboxylic acid monomers into silicone marine antifouling coatings, the hydrogen bonding effect is formed, and the existing coatings have poor adhesion and poor antifouling effect are solved, and a coating with high adhesion and excellent antifouling performance is achieved.
Patent Information
- Application Number
- CN202411551673.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-02-25
AI Technical Summary
The existing silicone marine antifouling coatings have poor adhesion to the substrate, cannot effectively prevent pollution in a water-static environment, and are prone to falling off on a large area after extended service time or friction collision.
The modified polysiloxane copolymer is prepared by acrylamide-siloxane-acrylic acid copolymer as the main framework, and the modified polysiloxane copolymer is introduced in two-step process, and amide groups and carboxylic acid groups are formed to form hydrogen bonding, and carboxylic acid monomers with catechol structure are introduced to enhance self-adhesion. The modified copolymer is blended with a hydrophobic polysiloxane resin and a cured coating is prepared by crosslinking reaction.
It achieves a good bonding effect on the substrate while maintaining the excellent anti-fouling performance of the coating, avoiding the problem of falling off during use.
Smart Images

Figure BDA0005115253350000021 
Figure BDA0005115253350000051 
Figure BDA0005115253350000061
Abstract
Description
Technical Field
[0001] The invention belongs to the field of marine antifouling coating technology and underwater coating protection technology, and particularly relates to a self-adhesive organic silicon marine antifouling coating Background Art
[0002] Marine biofouling generally refers to the process in which marine organisms indiscriminately adhere, grow and accumulate on various substrates immersed in seawater. Since the 1960s, the emergence of organotin marine antifouling coatings has effectively suppressed the harm caused by marine biofouling to the marine industry and made outstanding contributions to the development of the marine industry. However, with the development of science and technology and the improvement of environmental awareness, people have gradually realized that organotin substances can harm the survival of marine organisms, induce genetic mutations in marine organisms, and ultimately enrich through the food chain to endanger human life. In 2008, the International Maritime Organization and countries around the world gradually established complete laws and regulations to prohibit the use of organotin marine antifouling coatings. Therefore, the development of environmentally friendly marine antifouling coatings has become the focus of subsequent research and development in the field of marine antifouling.
[0003] Silicone marine antifouling coatings belong to the field of environmentally friendly fouling-releasing antifouling coatings. Based on lower surface free energy and lower elastic modulus, they utilize the relative movement between the ship and the seawater to achieve the prevention and control of fouling organisms and the removal of loosely adhered fouling organisms, and have great application prospects.
[0004] However, organosilicon marine antifouling coatings currently have poor adhesion to substrates and cannot effectively prevent fouling in static water environments, which urgently need to be improved. In actual use, as the service time increases, or due to friction or collision with other substances, large areas of the coating are very likely to fall off. This shortcoming has greatly limited the promotion and application of low surface energy organosilicon marine antifouling coatings. Summary of the invention
[0005] In order to overcome the problems that the existing organic silicon marine antifouling coating has poor adhesion to the substrate or the intermediate paint, and is easy to fall off during use, and the conventional modification method easily causes the coating surface energy to change, thereby affecting the antifouling performance of the cured coating, the present invention aims to provide an organic silicon marine antifouling coating with self-adhesive properties, and uses acrylamide-siloxane-acrylic acid copolymer as the main skeleton to prepare a modified polysiloxane copolymer in two steps. The amide group is introduced into the siloxane molecular structure by free radical copolymerization, and then the carboxyl group and the amide group react to form a hydrogen bond between the carboxyl group and the amide group in the molecular structure of the modified siloxane copolymer. Compared with the single amide group, the high acidity introduced by the carboxyl group strengthens the hydrogen bond, and the presence of the carboxyl group eliminates the secondary electrostatic repulsion, thereby further enhancing the strength of the hydrogen bond. In the second stage of preparing the modified polysiloxane copolymer, a carboxylic acid monomer with a catechol structure is introduced at the same time when the carboxylic acid group is introduced, thereby introducing a highly viscous catechol group into the modified copolymer, and the self-adhesiveness is further enhanced by additional hydrogen bond interactions. The final cured coating is prepared by blending the modified polysiloxane copolymer with the hydrophobic polysiloxane resin and undergoing a cross-linking reaction. Based on the principle of phase separation of polar and non-polar group polymers, the modified siloxane copolymer in the cured coating is mainly enriched in the coating-substrate region, while the flexible methylsiloxane structure with low surface free energy is enriched on the coating surface, thereby ensuring that the final cured coating still has excellent anti-fouling effect.
[0006] The present invention is implemented by the following technical solutions:
[0007] In a first aspect, the present invention provides a self-adhesive organic silicon marine antifouling coating, which comprises, by weight: (1) 80 to 100 parts of component A; (2) 15 to 30 parts of component B; (3) 4 to 12 parts of component C;
[0008] in,
[0009] Component A includes by weight:
[0010]
[0011] Component B includes by weight:
[0012] Curing agent 10-20 parts
[0013] Solvent B 20-40 parts
[0014] Component C includes by weight:
[0015] 8-15 parts of the first catalyst
[0016] Solvent C 20-30 parts;
[0017] Wherein, the modified polysiloxane copolymer is prepared by the following steps:
[0018] (1) In a reaction device protected by nitrogen and equipped with a stirring reflux device, acrylamide monomer, bisacrylamide monomer, MQ silicone resin with an unsaturated structure, initiator, and ethanol are added in sequence, and then the temperature is raised to 60-75° C. and the reaction is carried out at a stirring speed of 80-150 rpm for 6-10 hours to obtain a first-stage intermediate reaction product;
[0019] (2) then cooling the reaction system to room temperature, adding acrylic acid monomer, carboxylic acid monomer having a catechol structure, and the second catalyst in sequence, and reacting at a stirring speed of 100 to 200 rpm for 6 to 8 hours;
[0020] (3) Filter the precipitated product after the reaction, wash and filter it with deionized water for at least three times, and then dry it under vacuum conditions for 24 hours to obtain a modified polysiloxane copolymer.
[0021] Preferably, the acrylamide monomer is selected from acrylamide, methacrylamide and N-isopropylacrylamide.
[0022] Preferably, the bisacrylamide monomer is selected from one of N,N'-methylenebisacrylamide, N,N'-divinylethylenediamine and bis(acrylamide)methylvinylamine.
[0023] Preferably, the MQ type silicone resin having an unsaturated structure is selected from methyl vinyl MQ type silicone resin, and its M:Q value is ≥1.3:1, or the methyl vinyl MQ type silicone resin is liquid at 25°C.
[0024] Preferably, the initiator is selected from ammonium persulfate.
[0025] Preferably, the acrylic acid monomer is selected from acrylic acid and methacrylic acid.
[0026] Preferably, the carboxylic acid monomer having a catechol structure is selected from tannic acid.
[0027] Preferably, the second catalyst is selected from one of tetramethylethylenediamine, triethylamine and diethyldiamine.
[0028] Preferably, the weight ratio of the acrylamide monomer, the bisacrylamide monomer, the MQ silicone resin having an unsaturated structure, the initiator, ethanol, the acrylic acid monomer, the carboxylic acid monomer having a catechol structure, and the second catalyst is (5-10): (1-3): (20-35): (0.3-0.5): (30-50): (2-5): (1-3): (0.5-1).
[0029] Preferably, the hydrophobic silicone resin is selected from α,ω-dihydroxypolydimethylsiloxane having a viscosity of 2800-10000 mPa·s at room temperature.
[0030] Preferably, the auxiliary agent is selected from at least one of a wetting and dispersing agent, a defoaming agent and a leveling agent.
[0031] Specifically, the wetting and dispersing agent is selected from BYK116, BYK169 of BYK Company, and 901, 903 of Deqian Company.
[0032] Specifically, the defoaming agent is selected from BYK065, BYK066N of BYK Company, and EFKA2020 of Efka of the Netherlands.
[0033] Specifically, the leveling agent is selected from one of German BYK308, BYK310 and BYK373.
[0034] Preferably, the pigment filler is common in the field, and there is no special requirement. As a preferred embodiment, it is selected from but not limited to one of calcium carbonate, ferric oxide, titanium dioxide, barium sulfate, kaolin, and zinc oxide.
[0035] Preferably, the solvent A is selected from one of methanol, xylene and acetone.
[0036] Preferably, the curing agent is selected from one of tetraethyl orthosilicate, 3-(methacryloyloxy)propyltrimethoxysilane, 3-(isomethacryloyloxy)propyltrimethoxysilane and γ-methacryloyloxypropyltriisopropoxysilane.
[0037] Preferably, the solvent B is selected from one of acetone, butanone and acetylacetone.
[0038] Preferably, the first catalyst is selected from dibutyltin dilaurate, stannous octoate, and organic bismuth.
[0039] Preferably, the solvent C is selected from one of acetylacetone, cyclohexanone and toluene.
[0040] In a second aspect, the present invention provides a method for preparing the self-adhesive organosilicon marine antifouling coating described in the first aspect. The coating can be prepared in a conventional manner. First, component A, component B, and component C are prepared separately and stored in a sealed manner. During coating, components A, B, and C are mixed in a conventional mixing manner and applied immediately.
[0041] Preferably, the preparation method specifically comprises the following steps:
[0042] (1) In a dispersing and stirring device, a hydrophobic silicone resin, a modified polysiloxane copolymer, an auxiliary agent, and 50% of solvent A are sequentially added, and then dispersed at 100 rpm for 20 minutes. Then, pigments and fillers and 50% of solvent A are added to the dispersing and stirring device, and the dispersion is continued at the same speed for 20 minutes to prepare component A, and then sealed for storage;
[0043] (2) using a dispersing and stirring device to disperse the curing agent and solvent B at 50 rpm for 10 min, i.e., preparing component B, and then sealing and storing;
[0044] (3) Using a dispersing and stirring device at 50 rpm, the first catalyst and solvent C were dispersed for 10 min to prepare component C, which was then sealed and stored.
[0045] In a third aspect, the present invention provides a coating prepared from the self-adhesive silicone marine antifouling coating described in the first aspect, wherein component A, component B, and component C are uniformly mixed using conventional dispersion processes and equipment, and applied by spraying, rolling, brushing, etc., and cured for at least 48 hours to prepare a coating with a film thickness of 150 to 250 um.
[0046] Compared with the prior art, the present invention has the following beneficial effects:
[0047] (1) A modified polysiloxane copolymer is prepared by a two-step method using acrylamide-siloxane-acrylic acid copolymer as the main skeleton. An amide group is introduced into the siloxane molecular structure through a free radical copolymerization reaction, and then a hydrogen bond is formed between the carboxyl group and the amide group in the molecular structure of the modified siloxane copolymer through the reaction of the carboxyl group and the amide group.
[0048] (2) Compared with the single amide group, the high acidity introduced by the carboxyl group strengthens the hydrogen bonding effect, and the presence of the carboxyl group eliminates the secondary electrostatic repulsion, thereby further enhancing the strength of the hydrogen bonding effect. In the second stage of preparing the modified polysiloxane copolymer, a carboxylic acid monomer with a catechol structure is introduced at the same time as the carboxylic acid group, thereby introducing a highly viscous catechol group into the modified copolymer, further enhancing the self-adhesiveness through additional hydrogen bonding interactions.
[0049] (3) The final cured coating is prepared by blending the modified polysiloxane copolymer with the hydrophobic polysiloxane resin and undergoing a cross-linking reaction. Based on the phase separation principle of polar and non-polar group polymers, the modified siloxane copolymer in the cured coating is mainly enriched in the coating-substrate region, while the flexible methylsiloxane structure with low surface free energy is enriched on the coating surface, thereby ensuring that the final cured coating still has an excellent antifouling effect. DETAILED DESCRIPTION
[0050] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, without departing from the concept of the present invention, several variations and improvements can be made. These all belong to the protection scope of the present invention.
[0051] The coating of the present invention is carried out in sequence through a two-step method to carry out free radical copolymerization and carboxyl and amide group reactions, thereby preparing a modified polysiloxane copolymer, and then the modified polysiloxane copolymer is blended with a hydrophobic polysiloxane resin and finally prepared through a cross-linking reaction. A large number of dynamic covalent bonds and non-covalent bond interactions introduced by acrylamide and acrylic acid structures realize hydrogen bonding, and the high acidity of the carboxyl group ensures that the hydrogen bonding effect is more obvious, and effectively removes the reduction in hydrogen bond strength caused by secondary electrostatic repulsion. At the same time, additional high-density hydrogen bonding sites are introduced by the catechol structure, further strengthening the hydrogen bonding effect and enhancing the self-adhesiveness of the coating. The prepared coating has excellent bonding effect on various substrates, and the surface of the cured coating prepared by blending and cross-linking is still enriched with flexible, low surface free energy methylsiloxane structures, so the coating still maintains excellent anti-fouling effect.
[0052] The raw materials used in the examples are shown in Table 1. The specific implementation is not limited to the raw materials in Table 1, and corresponding products can be selected according to the above. Other raw materials used in the examples are all commercially available chemical reagents.
[0053] Table 1
[0054]
[0055]
[0056] Modified polysiloxane copolymer 1
[0057] The weight ratio of acrylamide monomer 2-1, bisacrylamide monomer 3-1, MQ silicone resin 4-2 with unsaturated structure, initiator, ethanol, acrylic acid monomer 5-1, carboxylic acid monomer with catechol structure, and second catalyst 6-2 is 8:3:25:0.3:40:3:1:0.7. The specific preparation method is as follows:
[0058] (1) In a reaction device protected by nitrogen and equipped with a stirring reflux device, acrylamide monomer, bisacrylamide monomer, MQ silicone resin with an unsaturated structure, initiator, and ethanol are added in sequence, and then the temperature is raised to 60° C. and the reaction is carried out at a stirring speed of 120 rpm for 6 hours to prepare a first-stage intermediate reaction product;
[0059] (2) The reaction system was then cooled to room temperature, and acrylic acid monomer, carboxylic acid monomer having a catechol structure, and the second catalyst were added in sequence, and the reaction was carried out at a stirring speed of 150 rpm for 8 hours;
[0060] (3) filtering the precipitated product after the reaction, washing and filtering with deionized water for at least three times, and then drying under vacuum conditions for 24 hours to prepare a modified polysiloxane copolymer.
[0061] Modified polysiloxane copolymer 2
[0062] The weight ratio of acrylamide monomer 2-2, bisacrylamide monomer 3-2, MQ silicone resin 4-1 with unsaturated structure, initiator, ethanol, acrylic acid monomer 5-1, carboxylic acid monomer with catechol structure, and second catalyst 6-1 is 5:1:35:0.4:30:2:2:0.5. The specific preparation method is as follows:
[0063] (1) In a reaction device protected by nitrogen and equipped with a stirring reflux device, acrylamide monomer, bisacrylamide monomer, MQ silicone resin with an unsaturated structure, initiator, and ethanol are added in sequence, and then the temperature is raised to 70° C. and the reaction is carried out at a stirring speed of 80 rpm for 8 hours to prepare a first-stage intermediate reaction product;
[0064] (2) The reaction system was then cooled to room temperature, and acrylic acid monomer, carboxylic acid monomer having a catechol structure, and the second catalyst were added in sequence, and the reaction was carried out at a stirring speed of 100 rpm for 6 hours;
[0065] (3) filtering the precipitated product after the reaction, washing and filtering with deionized water for at least three times, and then drying under vacuum conditions for 24 hours to prepare a modified polysiloxane copolymer.
[0066] Modified polysiloxane copolymer 3
[0067] The weight ratio of acrylamide monomer 2-3, bisacrylamide monomer 3-2, MQ silicone resin 4-2 with unsaturated structure, initiator, ethanol, acrylic acid monomer 5-2, carboxylic acid monomer with catechol structure, and second catalyst 6-1 is 10:2:20:0.5:50:5:3:1. The specific preparation method is as follows:
[0068] (1) In a reaction device protected by nitrogen and equipped with a stirring reflux device, acrylamide monomer, bisacrylamide monomer, MQ silicone resin with an unsaturated structure, initiator, and ethanol are added in sequence, and then the temperature is raised to 75° C. and the reaction is carried out at a stirring speed of 150 rpm for 10 hours to prepare a first-stage intermediate reaction product;
[0069] (2) The reaction system was then cooled to room temperature, and acrylic acid monomer, carboxylic acid monomer having a catechol structure, and the second catalyst were added in sequence, and the reaction was carried out at a stirring speed of 200 rpm for 7 hours;
[0070] (3) filtering the precipitated product after the reaction, washing and filtering with deionized water for at least three times, and then drying under vacuum conditions for 24 hours to prepare a modified polysiloxane copolymer.
[0071] Examples 1-5
[0072] The proportions of the three components A, B, and C of Examples 1-5 are shown in Table 2, and the specific proportions of the components of Examples 1-5 are shown in Table 3.
[0073] Table 2
[0074] Components Example 1 Example 2 Example 3 Example 4 Example 5 A 80 100 90 90 100 B 15 20 25 30 15 C 4 10 8 12 6
[0075] Table 3
[0076]
[0077]
[0078] According to Table 2 and Table 3, the preparation method of a self-adhesive organosilicon marine antifouling coating of Examples 1-5 is as shown in the following steps:
[0079] (1) In a dispersing and stirring device, a hydrophobic silicone resin, a modified polysiloxane copolymer, an auxiliary agent, and 50% of solvent A are sequentially added, and then dispersed at 100 rpm for 20 minutes. Then, pigments and fillers and 50% of solvent A are added to the dispersing and stirring device, and the dispersion is continued at the same speed for 20 minutes to prepare component A, and then sealed for storage;
[0080] (2) using a dispersing and stirring device to disperse the curing agent and solvent B at 50 rpm for 10 min, i.e., preparing component B, and then sealing and storing;
[0081] (3) using a dispersing and stirring device to disperse the first catalyst and solvent C at 50 rpm for 10 min, i.e., preparing component C, and then sealing and storing;
[0082] (4) Component A, component B, and component C are mixed uniformly using conventional dispersion processes and equipment, and applied by spraying, rolling, brushing, etc. After curing for at least 48 hours, a coating with a film thickness of 150 to 250 μm is prepared.
[0083] In actual application, the antifouling coating can be prepared by conventional methods of marine antifouling coatings, and is not limited to the above preparation method.
[0084] Comparative Example 1(Ordinary silicone low surface energy marine antifouling coating)
[0085] The common organosilicon low surface energy marine antifouling paint comprises the following raw materials in parts by weight: 90.0 parts of polysiloxane resin, 30.0 parts of pigments and fillers, 4.0 parts of cross-linking curing agent, 1.5 parts of catalyst, 0.5 parts of auxiliary agent and 10.0 parts of third solvent.
[0086] The polysiloxane resin is α, ω-dihydroxy polydimethylsiloxane with a viscosity of 10000 mPa·s; the pigment is zinc oxide; the cross-linking curing agent is tetraethyl orthosilicate; the catalyst is dibutyltin disilicate; the auxiliary agent is 0.5 parts of BYK161 dispersant from BYK; and the third solvent is xylene.
[0087] (1) 90.0 parts of α,ω-dihydroxy polydimethylsiloxane with a viscosity of 10000 mPa·s and 30.0 parts of micron-sized zinc oxide were added to a disperser and dispersed at 300 rpm for 30 min. Subsequently, 0.5 parts of BYK161 dispersant from BYK was added to the disperser at 200 rpm and dispersed for 30 min. The mixture was then ground with a sand mill to a fineness of less than 40 μm to prepare a pre-dispersed slurry and canned for standby use.
[0088] (2) 4.0 parts of tetraethyl orthosilicate and 10.0 parts of xylene were mixed evenly to prepare a crosslinking curing agent component, which was then canned for standby use; 1.5 parts of dibutyltin dioxysilicate and 20.0 parts of xylene were mixed evenly to prepare a catalyst component, which was then canned for standby use;
[0089] (3) Before use, the pre-dispersed slurry, the cross-linking curing agent component, and the catalyst component are stirred uniformly according to the ratio. After the obtained coating is applied and cured, a common organic silicon low surface energy marine antifouling coating with a thickness of 150 to 250 μm is obtained.
[0090] Comparative Example 2
[0091] Compared with Example 1, there is no hydrophobic silicone resin, and the remaining components and their weight parts are the same, and the preparation process is also the same as that of Example 1.
[0092] <Specific test experiments and conditions>
[0093] Test 1: Surface Free Energy
[0094] The contact angles of deionized water and diiodomethane on the surface of the cured coating were measured using the XG-CAMC3 fully automatic contact angle meter produced by Shanghai Xuanzhun Instrument Co., Ltd. Before the measurement, the coating surface needs to be cleaned with anhydrous ethanol and dried, and then the surface free energy of the coating is calculated according to the Owens two-liquid method.
[0095] Test 2: Pull-off method to measure adhesion after 100 days of seawater immersion (steel plate, epoxy intermediate paint)
[0096] The BGD500 digital semi-automatic adhesion tester produced by Guangzhou Biaogeda Precision Instrument Co., Ltd. was used to measure the adhesion of the coating applied on the corresponding substrate or epoxy intermediate paint. The steel plate needs to be polished with 800-grit sandpaper before use, and the epoxy intermediate paint used is the epoxy micaceous iron intermediate paint produced by Shanghai Jinsi Di. Before the test, it needs to be immersed in sterilized seawater for 100 days, and then taken out and dried for testing.
[0097] Test 3: Antifouling performance
[0098] A suspension containing at least 108 units of Streptococcus salivarius was dispersed in 20 ml of tryptic soy broth and incubated at 38°C, 5% CO2 for 2 hours. The suspension was then further diluted and inoculated in agar supplemented with 5% sheep blood and incubated at 38°C, 5% CO2 for 48 hours, and then the units containing six colonies were dispersed in 10 ml of tryptic soy broth. Subsequently, 20 ml of the above bacterial suspension was covered on the coating of 10×5 cm area and incubated at 38°C, 5% CO2 for 24 hours. After the incubation, each sample needed to be rotated and rinsed in 45 ml of distilled water for 30 seconds, and then rinsed with 50 ml of distilled water to remove non-sticky materials. The surface-adherent bacteria were observed using a Simga300 scanning electron microscope produced by Carl Zeiss, Germany.
[0099] The specific test results of Examples 1-5 and Comparative Examples 1-2 are shown in Table 4.
[0100] Table 4
[0101]
[0102] The above tests confirm that the embodiments have good adhesion and excellent antifouling effect.
[0103] The above is a description of the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.
Claims
1. A self-adhesive organosilicon marine antifouling coating, characterized in that: In parts by weight, it comprises: (1) 80 to 100 parts of component A; (2) 15 to 30 parts of component B; (3) 4 to 12 parts of component C; in, Component A includes by weight: Component B includes by weight: Curing agent 10-20 parts Solvent B 20-40 parts Component C includes by weight: 8-15 parts of the first catalyst Solvent C 20-30 parts; Wherein, the modified polysiloxane copolymer is prepared by the following steps: (1) In a reaction device protected by nitrogen and equipped with a stirring reflux device, acrylamide monomer, bisacrylamide monomer, MQ silicone resin with an unsaturated structure, initiator, and ethanol are added in sequence, and then the temperature is raised to 60-75° C. and the reaction is carried out at a stirring speed of 80-150 rpm for 6-10 hours to obtain a first-stage intermediate reaction product; (2) then cooling the reaction system to room temperature, adding acrylic acid monomer, carboxylic acid monomer having a catechol structure, and the second catalyst in sequence, and reacting at a stirring speed of 100 to 200 rpm for 6 to 8 hours; (3) Filter the precipitated product after the reaction, wash and filter it with deionized water for at least three times, and then dry it under vacuum conditions for 24 hours to obtain a modified polysiloxane copolymer.
2. The antifouling coating according to claim 1, characterized in that The acrylamide monomer is selected from acrylamide, methacrylamide, and N-isopropylacrylamide; the bisacrylamide monomer is selected from N,N'-methylenebisacrylamide, N,N'-divinylethylenediamine, and bis(acrylamide)methylvinylamine.
3. The antifouling coating according to claim 1, characterized in that The MQ type silicone resin with an unsaturated structure is selected from a methyl vinyl MQ type silicone resin, and its M:Q value is ≥1.3:1, or the methyl vinyl MQ type silicone resin is liquid at 25°C.
4. The antifouling coating according to claim 1, characterized in that The carboxylic acid monomer having a catechol structure is selected from tannic acid.
5. The antifouling coating according to claim 1, characterized in that: The second catalyst is selected from one of tetramethylethylenediamine, triethylamine and diethyldiamine.
6. The antifouling coating according to claim 1, characterized in that: The weight ratio of acrylamide monomer, bisacrylamide monomer, MQ silicone resin with unsaturated structure, initiator, ethanol, acrylic acid monomer, carboxylic acid monomer with catechol structure and second catalyst is (5-10): (1-3): (20-35): (0.3-0.5): (30-50): (2-5): (1-3): (0.5-1).
7. The antifouling coating according to claim 1, characterized in that: The first catalyst is selected from dibutyltin diosilicate, stannous octoate, and organic bismuth.
8. A method for preparing an antifouling coating according to any one of claims 1 to 7, characterized in that: The specific steps include: (1) In a dispersing and stirring device, a hydrophobic silicone resin, a modified polysiloxane copolymer, an auxiliary agent, and 50% of solvent A are sequentially added, and then dispersed at 100 rpm for 20 minutes. Then, pigments and fillers and 50% of solvent A are added to the dispersing and stirring device, and the mixture is dispersed at the same speed for 20 minutes to obtain component A, which is then sealed and stored; (2) using a dispersing and stirring device to disperse the curing agent and solvent B at 50 rpm for 10 min to obtain component B, which is then sealed and stored; (3) Using a dispersing and stirring device, the first catalyst and solvent C are dispersed at 50 rpm for 10 min to obtain component C, which is then sealed and stored.
9. An antifouling coating prepared by the antifouling coating according to any one of claims 1 to 7, characterized in that: Component A, component B and component C are mixed evenly, applied on the substrate, and cured for at least 48 hours to prepare a coating with a film thickness of 150 to 250 um.
Citation Information
Patent Citations
Functionalized modified fouling release type marine antifouling paint
CN118813135A